3 - Towards Evaluating a Higher Education Residence Environment that is Conducive to Learning, Development and Success - Willem Petrus Wahl (Journal of Higher Education in Africa, 2013)
The higher education residence environment has traditionally been perceived as mere buildings that provide accommodation to students, especially in Africa. However, for more than a decade now, research on Living Learning programmes has shown how residence-based programmes can create inclusive communities where the academic project of institutions is successfully integrated with the living environment of students. This integration creates an environment that is conducive to learning, development, and success. The aim of this article is to analyse some of the latest empirical research on Living Learning programmes and then make a comparison with the theory on student learning and development, in order to enable practitioners to evaluate their own residence environments to become more conducive to learning, development, and success. Ten questions are generated through this comparative analysis and it is recommended that practitioners in Africa use it as an evaluative framework within their institution’s residence environment.